Fundamental elements and characteristics for telling stories using data - Borges, Mariana (2022)
One of the biggest challenges today is how to present data to users in a clear and easy way in different domains of application. One way to do this is to tell stories with data, as this makes it possible to improve user engagement and understanding of a given context. By using narrative elements, it is possible to provide readers with better explanations of what is being presented. To understand the research scenario about this topic, a systematic review of the literature was performed, through a snowballing procedure. As results, the main characteristics of these visualizations were identified as well as the genres and tools used in their development, and the main visualization techniques used. These results demonstrate that the most used genres are slideshows, data comics, annotated charts, magazine style, and flow chart. One of the main open questions is about the genres used for each - different - type of data, demonstrating that the topic is emerging and necessary.